2021
DOI: 10.1002/wer.1521
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of textile azo dye Novacron Red using bacterial monoculture and consortium: Response surface methodology optimization

Abstract: The present study was intended toward the optimization of a textile dye Novacron Red decolorization by single and mixed culture of Bacillus strains namely, B. firmus, B. filamentosus and B. subterraneus. Optimization of dye decolorization using Bacillus monocultures was conducted using central composite design. The maximum dye decolorization achieved under optimized conditions for B. firmus, B. filamentosus and B. subterraneus was 89.24%, 88.28% and 88.45%, respectively. The effect of various consortia of sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…However, the study discovered that the strains in the coculture method lacked the potential to efficiently exert their synergistic impact in increasing enzyme production. Furthermore, some researchers have suggested that single strains may be a more preferable option for dye decolorization compared to mixed cultures. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the study discovered that the strains in the coculture method lacked the potential to efficiently exert their synergistic impact in increasing enzyme production. Furthermore, some researchers have suggested that single strains may be a more preferable option for dye decolorization compared to mixed cultures. , …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some researchers have suggested that single strains may be a more preferable option for dye decolorization compared to mixed cultures. 40,6 2.4. Enzyme Activity in Dye Decolorization.…”
Section: Isolation and Identification Of CV Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization of culture conditions is important for the development of any biotreatment processes for removing dyes contamination [23,24]. To explore the effect of different factors on Pseudomonas aeruginosa WYT degradation of VB4, single colonies of VB4 discoloration were inoculated and grown in 50 mL flasks containing 10 mL of LB medium at 30ºC and 200 rpm.…”
Section: Effect Of Different Degradation Parametersmentioning
confidence: 99%
“…Earlier, B. subtilis (K7), B. filamentosus (K1) and Lysinibacillus cresolivorans (K5) were isolated from desert soil samples of Cholistan, Pakistan and several thermophilic proteases isolated from B. filamentosus (K1) show optimum temp at 65°C, whereas these proteases can de-stain the blood from cotton cloth and de-hair the cow’s skin (Cresolivorans et al, 2021). The monoculture and consortium of B. filamentosus, B. firmus and B. subterraneus show decolorization of Novacron Red textile dye (Guembri et al, 2021). These studies show the use of B. filamentosus , the constitution of this consortia, and its potential application in textile water treatment.…”
Section: Introductionmentioning
confidence: 99%